Percobaan Kedokteran terhadap Hewan Hidup dalam Perspektif Hukum Islam - M. Kasim; Aprianti, Farida; Sa'adal Jannah; Rezki, Nurayu (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2021)
This study aims to determine the legal experimental medicine on live animals from the perspective of contemporary fiqh, as well as to find out the opinions of the scholars in understanding the problem. This research uses descriptive qualitative research (non-statistical) which focuses on the study of manuscripts and texts using a normative juridical approach. The results of the study found that some scholars allowed the use of animals in an experiment. However, some scholars do not allow its use without knowing the ethics in experiments. The reason is that this never existed in the health sector at the time of the Prophet Muhammad. However, if the user is carried out without an urgent need, then the law is not allowed.